WAYS AND MEANS OF DEVELOPING COMMUNICATIVE QUALITIES AND COMMUNICATION SKILLS OF AN EDUCATOR - Otajonov Jamshid Mashrabjonovich; Dadajonova Zarnigor Foziljon qizi (Zeta Repository, 2023)
The article talks about ways and means of developing communication skills, developing communication skills and developing them in preschool teachers.